Research: an insight on how it is valued by Portuguese and English teacher educators. Issue 4 (2nd October 2019) - Sousa, Rita Tavares de; Lopes, Amélia; Boyd, Pete
ABSTRACT: The quality of how teachers are being prepared is seen as a priority in the twenty-first century and engagement with research is often considered a crucial element of initial teacher education programmes. Institutional and national contexts have an impact in the way research is valued. This paper investigates the perspectives of Portuguese and English teacher educators towards the value given to research in initial teacher education. Interviews were completed with teacher educators working within different kinds of higher education institutions—university, polytechnic and teaching-led university. Results suggest that research has a significant presence and relevance in all cases but is valued differently